Gradual Evolution. - Savage, Neil (Communications of the ACM, 2014)
The article reports on dynamically typed programming languages and their adoption of static typing towards growth. These include JavaScript, Python and Perl. It mentions their assessment of programs for errors which alleviates writing of applications despite of hidden bugs. It notes an annotation and its role as a metadata that determines the function for a specific variable. An overview of the continuum of development languages and the views of Microsoft Research Technical Fellow Anders Hejlsberg on the TypeScript program is also presented.